Caffeine mouth rinse enhances performance, fatigue tolerance and reduces muscle activity during moderate-intensity cycling - de Albuquerque Melo, A.; Bastos-Silva, V.; Arruda Moura, F.; Rico Bini, R.; Eduardo Lima-Silva, A.; Gomes de Araujo, G. (Biology of Sport, 2021)
We investigated the effects of caffeine mouth rinse on endurance performance, muscle recruitment (i.e., electromyographic activity of the vastus lateralis and rectus femoris), rating of perceived effort and heart rate. Twelve physically-active healthy men cycled at 80% of their respiratory compensation point until task failure. The participants rinsed their mouths for 10 seconds with placebo (PLA, 25 mL of a solution composed of non-caloric mint essence) or caffeine (CAF, 25 mL of 1.2% of anhydrous caffeine concentration with noncaloric mint essence) every 15 minutes of exercise. Time until exhaustion increased 17% (effect size = 0.70) in CAF compared to PLA (p = 0.04). The wavebands of low-frequency electromyographic activity (EMG) of the vastus lateralis and rectus femoris was lower in CAF group than PLA at 50% of the time until exhaustion (p = 0.04). The global EMG signal was lower in CAF group than PLA at 100% of the time until exhaustion (p = 0.001). The rating of perceived effort pooled was higher in CAF mouth rinse (p = 0.001) than PLA group. No effect was found on the heart rate between the groups (p > 0.05). Caffeine mouth rinse increases endurance performance, rating of perceived effort and decreases muscle activity during a moderate-intensity exercise.